Cities vs. agriculture: a review of intersectoral water re-allocation - Molle, Francois; Berkoff, J. (Wiley, 2009)
Water demand management, or making better use of the water we have - as opposed to augmenting supply - is increasingly proposed as a way of mitigating water-scarcity problems. Moving water away from agriculture to uses with higher economic value is one of the main measures widely seen as desirable. Sectoral "allocation stress? is seen as resulting from the disproportionate share, and inefficient use of water in the agricultural sector. This apparent misallocation is often attributed to the failure of government to allocate water rationally. This paper revisits this commonly-accepted wisdom and examines the nature of urban water scarcity, showing the importance of economic and political factors, shaped by incentives to decision-makers, and sometimes compounded by climatic conditions. It shows that cities' growth is not generally constrained by competition with agriculture. In general, rather than using a narrow financial criterion, cities select options that go along the "path of least resistance,? whereby economic, social and political costs are considered in conjunction. The question of allocation stress is thus reframed into an inquiry of how transfers effectively occur and can be made more effective.